KEJADIAN BERAT BAYI LAHIR RENDAH DI RSD BALUNG JEMBER - Asri Iman sari; Putri Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2021)
Low birth weight (LBW) is a condition in which the birth weight of a baby is less than 2500 gram during an hour after birth. In 2015, WHO recorded the incidence of LBW in Indonesia was on the ninth level with a percentage of 15.5%. East Java Central Bureau of Statistics also recorded the incidence of LBW in 2017 was 6.01%. Moreover, the incidence of LBW in Jember Regency was 6.11%. There is a relationship between the incidence of LBW with perinatal and neonatal mortality. Internal factors which might cause LBW are the age of the pregnant mother and parity. This study used a descriptive-analytical method with a retrospective approach. The study population were 421 LBW babies treated at Balung Hospital from January until December 2019. The result of this study shows that the mother of 291 study participants was at reproductive age (69.1%) and the parity of 370 mothers of the study participants was a low-risk pregnancy. We concluded that there was no relationship between age and parity of mother with LBW incidence.